1996
DOI: 10.5962/bhl.title.87967
|View full text |Cite
|
Sign up to set email alerts
|

Tailed frogs : distribution, ecology, and association with timber harvest in northeastern Oregon /

Abstract: Tailed frogs (Ascaphus truei) were found in 42 of 80 streams surveyed in Union, Umatilla, Wallowa, and Baker Counties in 1992. At least three size classes of larvae were identified in seven of the streams, thereby suggesting that larvae transform after spending 3 or more years in the streams. The amount of cobble and fines in the streambed best predicted abundance of larvae, whereas, cobble, boulders, slope gradient, and stream buffers best predicted abundance of adults. SummaryThis study was designed to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For example, several studies occurring in coastal streams traversing harvested forests have found a negative relationship between stream amphibians and unconsolidated geologies (Diller and Wallace 1996, Wilkins and Peterson 2000), but a study in an unharvested preserve found stream amphibians to be relatively abundant in coastal streams on unconsolidated geologies (Adams and Bury 2002). Several studies have found a negative relationship between presence or abundance of stream amphibians and previous timber harvest in the Pacific Northwest (Corn and Bury 1989, Stoddard and Hayes 2005), but stream amphibians are sometimes abundant in second‐growth stands (Diller and Wallace 1996, 1999; Wilkins and Peterson 2000) and site level factors may mediate the effects of timber harvest (Bull and Carter 1996, Raphael et al 2002, Welsh and Lind 2002).…”
mentioning
confidence: 99%
“…For example, several studies occurring in coastal streams traversing harvested forests have found a negative relationship between stream amphibians and unconsolidated geologies (Diller and Wallace 1996, Wilkins and Peterson 2000), but a study in an unharvested preserve found stream amphibians to be relatively abundant in coastal streams on unconsolidated geologies (Adams and Bury 2002). Several studies have found a negative relationship between presence or abundance of stream amphibians and previous timber harvest in the Pacific Northwest (Corn and Bury 1989, Stoddard and Hayes 2005), but stream amphibians are sometimes abundant in second‐growth stands (Diller and Wallace 1996, 1999; Wilkins and Peterson 2000) and site level factors may mediate the effects of timber harvest (Bull and Carter 1996, Raphael et al 2002, Welsh and Lind 2002).…”
mentioning
confidence: 99%